2019
DOI: 10.1111/and.13441
|View full text |Cite
|
Sign up to set email alerts
|

Parameters predicting sperm retrieval rates during microscopic testicular sperm extraction in nonobstructive azoospermia

Abstract: The aim of this study was to investigate the predictive value of the parameters that might have an effect on the success of microscopic testicular sperm extraction (micro-TESE) in infertile patients with nonobstructive azoospermia (NOA). Between 2003 and 2014, 860 patients with NOA were retrospectively analysed. The effect of age, infertility duration, history of varicocelectomy, herniorrhaphy or orchiopexy, presence of solitary testis, tobacco use, previous testicular biopsy results, history of orchitis, usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 21 publications
(31 reference statements)
3
24
1
1
Order By: Relevance
“… Articles Characteristics Mean Age (years, male/female) Varicocele Grade Varicocele Repair Methods Semen Analysis Pregnancy Modality Surgical Sperm Retrieval Method Kizilkan Y, et al. (2019) [ 11 ] 34.4/NR NR NR Azoospermia NR Micro-TESE Zampieri N, et al. (2013) [ 12 ] 33.1/NR Grade III Subinguinal microsurgery Azoospermia ICSI TESE Haydardedeoglu B, et al.…”
Section: Resultsmentioning
confidence: 99%
“… Articles Characteristics Mean Age (years, male/female) Varicocele Grade Varicocele Repair Methods Semen Analysis Pregnancy Modality Surgical Sperm Retrieval Method Kizilkan Y, et al. (2019) [ 11 ] 34.4/NR NR NR Azoospermia NR Micro-TESE Zampieri N, et al. (2013) [ 12 ] 33.1/NR Grade III Subinguinal microsurgery Azoospermia ICSI TESE Haydardedeoglu B, et al.…”
Section: Resultsmentioning
confidence: 99%
“…The situation is quite different for the predictive role of serum T on the chances of sperm retrieval, since studies in the field have reported conflicting results. We were able to individuate 14 studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42] who clearly reported the relationship between serum T levels and sperm retrieval rates (SRR) (Table 1). Studies differed for study design, inclusion criteria, and patients' characteristics.…”
Section: Relationship Between Serum Hormones Levels and Sperm Retrievalmentioning
confidence: 99%
“…mTESE is considered to be the gold standard surgical procedure for sperm retrieval in NOA patients. 3 Studies documented that mTESE is 1.5-fold more effective than random multiple-biopsy TESE, which is 2-fold more effective than testicular aspiration. There are some indicators that might be predictive for successful SR, one of them is testicular size.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Kizilkan et al study showed higher testicular volumes were found to increase sperm retrieval in mTESE, and volumes above 11 ml were significantly associated with successful results. 3 Marconi et al reported that men with a testicular volume of less than 8 ml and FSH greater than 12.4 IU had an approximately 30% chance of testicular SR by mTESE. In a study of 106 men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation